Proceso de transformación de persona natural a compañía de responsabilidad limitada, con el traspaso de inventario de la empresa “ELECTRO OFERTAS” ubicada en la ciudad de Cayambe, Provincia de Pichincha, durante el año 2014. - Olmedo Tipan, Edison Byron (2015)
This research deals with the transformation of a company with the status of a natural person’s enterprise into a limited liability company, taking into account all the legal steps to be followed, which are provided by the Superintendencia de Compañías. This company’s trade name is "Electro Ofertas" and is located in Cayambe City, Pichincha Province. Electro Ofertas offers domestic appliances, computer equipment, furniture, technological equipment, minor machinery, industrial machinery design and motorcycles. During the transformation process, the following steps were executed: • Reservation of the name for the new company. • Statutes’ elaboration for the new company. • Opening of a business account for the capital integration. • Getting of a public deed. • Approval of the statutes by the Superintendencia de Compañías. • Publication of an extract of the constitution of the new company on an accounting journal. • Registration of the new company in the Commercial Register of the Cayambe Canton. • Executionof the first meeting of the company’s shareholders. • Registration of appointments in the Commercial Register of the Cayambe Canton. • Getting the RUC.